Application scope of prediction model for interval grey number based on GM (1, 1) - Lianming Zhao; Bo Zeng (Institute of Advanced Engineering and Science, 2014)
Prediction models have some modeling conditions and application scope, we can use them to simulate or predict only when the models are satisfies those conditions. In this paper, we study the application scope of prediction model for interval grey number based on GM (1, 1) through the mathematical derivation. The reslt shown that when the parameters of prediction model for interval grey number satisfied or ，prediction model for interval grey number is meaningless. The research achievements are of great significance in enrich the grey models and integrate the gray theory with practical issues. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4499